Simultaneous determination of serum homocysteine, cysteine, and methionine in patients with schizophrenia by liquid chromatography–tandem mass spectrometry. (25th March 2022) - Li, Zhenguo; Liu, Mingli; Chen, Chunwu; Pan, Yongqiang; Cui, Xueting; Sun, Jian; Zhao, Furong; Cao, Yunfeng
Abstract: Schizophrenia is a debilitating psychiatric disorder affecting approximately 1% of the population worldwide. Disturbances in the homocysteine metabolism are an important factor in the pathophysiology of schizophrenia. In this research, a novel validated liquid chromatography–tandem mass spectrometry (LC–MS/MS) quantification procedure was developed to investigate three significant compounds of homocysteine metabolism: homocysteine, cysteine, and methionine in patients with schizophrenia and healthy controls. Sample preparation involved a reduction with dithiothreitol followed by protein precipitation, and the chromatographic runtime was 2 min. The LC–MS/MS method was validated according to CLSI C62‐A and the Chinese Guidance for Liquid Chromatography and Mass Spectrometry Clinical Application. The performance of the method was excellent with a coefficient of variation for precision in the range of 0.5–6.9%, an accuracy of 90.4–101.6%. In addition, the practical applicability of the method was demonstrated by applying it in the routine sample analysis for a schizophrenic patient. Increased homocysteine levels and decreased cysteine levels were observed in the patient with schizophrenia. These results indicate that the activity of the transsulfuration pathway may play a key role in the pathogenesis of schizophrenia.